2021
DOI: 10.1016/j.isci.2021.102390
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial SIRT3 regulates myofibroblast metabolic shifts in diabetic kidneys

Abstract: Summary Defects in endothelial cells cause deterioration in kidney function and structure. Here, we found that endothelial SIRT3 regulates metabolic reprogramming and fibrogenesis in the kidneys of diabetic mice. By analyzing, gain of function of the SIRT3 gene by overexpression in a fibrotic mouse strain conferred disease resistance against diabetic kidney fibrosis, whereas its loss of function in endothelial cells exacerbated the levels of diabetic kidney fibrosis. Regulation of endothelial cell S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 54 publications
1
59
0
Order By: Relevance
“…41 Studies on diabetic mice showed that loss of Sirt3 favoured the EMT of renal tubular epithelial cells through the TGF-β/Smad3 axis, and exacerbated kidney fibrosis. 42 Accordingly, Sirt3 expression protects the liver, heart and kidney from the development of fibrosis, as demonstrated in humans and animal models. 158 In particular, studies performed both in vitro and in a mouse model of renal fibrosis demonstrated that up-regulation of Sirt3 activity resulted in a reduced fibrotic response, through regulation of mitochondrial dynamics and the NF-kB/TGF-β1/Smad signalling pathway.…”
Section: Sirt3 and Fibrosismentioning
confidence: 97%
See 1 more Smart Citation
“…41 Studies on diabetic mice showed that loss of Sirt3 favoured the EMT of renal tubular epithelial cells through the TGF-β/Smad3 axis, and exacerbated kidney fibrosis. 42 Accordingly, Sirt3 expression protects the liver, heart and kidney from the development of fibrosis, as demonstrated in humans and animal models. 158 In particular, studies performed both in vitro and in a mouse model of renal fibrosis demonstrated that up-regulation of Sirt3 activity resulted in a reduced fibrotic response, through regulation of mitochondrial dynamics and the NF-kB/TGF-β1/Smad signalling pathway.…”
Section: Sirt3 and Fibrosismentioning
confidence: 97%
“…37,38 Sirt3 dampens the canonical TGF-β signalling pathway, also due to the deacetylation of Smad3, thus reducing the cellular profibrotic responses. 40,42,43,93 Sirt4 can exert antifibrotic activity by deacetylating Smad4. 47 Interestingly, Sirt6 has interacting partners belonging to both the canonical and non-canonical TGF-β signalling pathways, and its effects are antifibrotic.…”
Section: Tgf-β Pathwaymentioning
confidence: 99%
“…In our laboratory, we have investigated crucial molecules that provide endothelial cell stability integrity, such as endothelial SIRT3, which is an essential mitochondrial protein and maintains the balance of fuel preference between healthy and damaged endothelial cells in diabetes [ 39 , 146 , 147 ]. Another study demonstrates that endothelial FGFR1 signaling is also important for endothelial cell heath in diabetic kidneys and the heart [ 148 , 149 ].…”
Section: Therapeutics and Perspectivesmentioning
confidence: 99%
“…Pathological stimuli such as inflammation, diabetes and ageing influence EndMT events in the kidneys [ 69 ]. Endothelial SIRT3, the nuclear receptor glucocorticoid receptor (GR) and cell surface FGFR1 are critical regulators of TGFβ signaling and EndMT in diabetic kidneys [ 70 , 71 , 72 , 73 ]. The kidneys of diabetic mice showed both progressive glomerular sclerosis and tubulointerstitial fibrosis, which was associated with approximately 40% of all FSP-1-positive cells and 50% of αSMA-positive stromal cells were CD31-positive [ 74 ].…”
Section: Lncrnas Involvement In the Regulation Of Endmtmentioning
confidence: 99%